Managing enterprise risk : what the electric industry experience implies for contemporary business - Leggio, Karyl; Bodde, David L.; Taylor, Marilyn L.; ScienceDirect eBooks (Amsterdam ; Boston ; London : Elsevier, 2006)
The increasing complexity of emerging business models and a growing societal concern with the integrity of financial reporting now leads to new emphases on accountability within large, publicly traded energy corporations. This book emphasizes the implications these issues have in the electric industry, a traditional infrastructure that underlies the digital society and now faces extraordinary environmental, regulatory, and technological uncertainties. Informs professionals in a variety of fields of the best current thinking on business riskhow it can be understood, how it can be managed, and how it can be communicated to diverse constituencies.
Part I. The Nature of Risk in the Electric Sector -- Part II. Current Approaches to Managing Risk: Their Power and Limitations -- Part III Emerging Risk Management Techniques -- Part IV. An Integrated Approach to Understanding, Managing, and Communicating Risk.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Electric utilities -- Risk management -- United States; TECHNOLOGY & ENGINEERING -- Power Resources -- Electrical; United States; Electronic books